SUSTAINABLE DEVELOPMENT (CONCEPTS, OBJECTIVES AND DIMENSIONS, INDICATORS OF MEASUREMENT) (CAHIERS MAGELLANES-NS, 2024)
This study seeks to provide a comprehensive analysis of the concept of sustainable development by exploring its objectives, dimensions and benchmarks. Initially, the historical evolution of the concept of development was reviewed, focusing on its essential role in improving quality of life and community service. In addition, different definitions and concepts of sustainable development have been analysed from a theoretical perspective, helping to clarify the nuances between different frameworks.The study also included a practical application of theoretical frameworks for sustainable development through a specific case study, allowing a deeper understanding of how these frameworks are implemented on the ground. Through this approach, the close relationship between indicators, dimensions and challenges to sustainable development was highlighted, with a focus on how to overcome these challenges through optimal use of available resources.Finally, the study aims to make new and useful contributions to sustainable development, providing practical recommendations to promote sustainable development in different societies, drawing on best practices and successful experiences to achieve environmental, social and economic sustainability.Keywords: sustainable development, economic development, environmental development, social development.This study aimed at exploring sustainable development in its concepts, objectives and dimensions, indicators of measurement, analysis of theoretical frameworks and their application to this particular context, Where a review of the historical development of development was presented, focusing on its role in the service of society, Definitions and concepts of sustainable development were also reviewed and analysed, and a practical case study of the application of those theoretical frameworks was presented, Later, as such, the research sought to shed light on the close relationship between indicators, dimensions and challenges and to make a useful contribution to understanding how to promote sustainable development through optimal utilization of the Earth's available resources.